Efektivitas Program Emotion-Focused Couples Communication Berbasis Daring terhadap Peningkatan Kepuasan Pernikahan Selama Pandemi COVID-19 pada Wanita Menikah di Indonesia - Callista, Maria Fionna; Maharini, Mutiara; Syafana, Mahira; Nurwianti, Fivi (Universitas Muhammadiyah Metro, 2024)
This study aims to determine the effectiveness of the online Emotion-Focused Couples Communication Program on increasing marital satisfaction during the COVID-19 pandemic among married women in Indonesia. This research uses a mixed-method approach. The sampling technique employed is non-probability sampling, specifically convenience or accidental sampling. Qualitative data was collected through observation, interviews, and verbal feedback from participants in each therapy session. Quantitative data collection utilized participant demographic questionnaires (personal data and description of insomnia problems), PCI (Primary Communication Inventory), and DAS (The Dyadic Adjustment Scale). The study results indicate that qualitatively, all participants experienced an improvement in their communication skills with their husbands. Additionally, this data is supported by significant statistical tests and an increase in the average score of husbands' perception of their wives' communication abilities. Qualitatively, all participants felt that the group intervention had a positive impact.